2022
DOI: 10.1038/s41598-022-17620-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multi-class and fusion of multiple single-class SegNet model for mapping karst wetland vegetation using UAV images

Abstract: Wetland vegetation classification using deep learning algorithm and unmanned aerial vehicle (UAV) images have attracted increased attentions. However, there exist several challenges in mapping karst wetland vegetation due to its fragmentation, intersection, and high heterogeneity of vegetation patches. This study proposed a novel approach to classify karst vegetation in Huixian National Wetland Park, the largest karst wetland in China by fusing single-class SegNet classification using the maximum probability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Its core component is an encoder network and corresponding decoder network, followed by a pixel‐level classifier, which outputs the probability map of the K channel, where K is the number of classification categories. Compared with other models, SegNet has fewer training parameters, smaller memory occupation, and shorter network training time (Deng et al, 2022; Jiang et al, 2020; Manickam et al, 2020). A comparison of accuracy evaluation results using six indexes (Accuracy, Precision, Recall, F1 value (weights both precision and recall), receiver operating characteristic (ROC) curve, and area under ROC curve (AUC)) revealed that SegNet ranked first for ephemeral gully recognition in the hilly and gully region of the Loess Plateau, followed by Recurrent residual U‐Net (R2U‐Net) and U‐Net (Liu et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Its core component is an encoder network and corresponding decoder network, followed by a pixel‐level classifier, which outputs the probability map of the K channel, where K is the number of classification categories. Compared with other models, SegNet has fewer training parameters, smaller memory occupation, and shorter network training time (Deng et al, 2022; Jiang et al, 2020; Manickam et al, 2020). A comparison of accuracy evaluation results using six indexes (Accuracy, Precision, Recall, F1 value (weights both precision and recall), receiver operating characteristic (ROC) curve, and area under ROC curve (AUC)) revealed that SegNet ranked first for ephemeral gully recognition in the hilly and gully region of the Loess Plateau, followed by Recurrent residual U‐Net (R2U‐Net) and U‐Net (Liu et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The improved U-Net model was named ISDU-Net, and ISDU-Net was compared with the FCN, SegNet, and U-Net models to analyze the qualitative and quantitative results [51][52][53][54][55][56][57][58][59][60][61][62].…”
Section: Comparative Analysis Of Improved U-net and Classical Network...mentioning
confidence: 99%
“…As Chen et al [5] show, the task of segmenting livestock animals such as cows and pigs in images has accompanied the rise of deep learning over traditional computer vision techniques. In general, deep learning has become extensively used for semantic segmentation, with SegNets and its derivations being one of the most cited deep networks to this end [6]- [8]. One weakness of SegNets, however, is that they usually fail to correctly classify pixels that are near object edges, therefore producing sub-optimal outlines [9].…”
Section: Introductionmentioning
confidence: 99%